THE REFLECTION OF HEROISM IN THE NOVELS OF E.HEMINGWAY - G’ulomova Shahlo Mansur qizi; Khamitov Eldorbek Erkin o‘g‘li (TADQIQOTLAR.UZ, 2024)
Hemingway’s characters often grapple with personal battles that test their endurance and ethical beliefs, reflecting the author’s own experiences with war and existential contemplation. The “Code Hero,” a central figure in Hemingway’s narratives, embodies qualities such as honor, bravery, and a stoic acceptance of fate. Through sparse prose and a focus on subtext, Hemingway’s writing style allows readers to infer the depth of heroism present in his characters’ actions and decisions. Works like “The Old Man and the Sea,” “For Whom the Bell Tolls,” and “A Farewell to Arms” showcase varied aspects of heroism, from the solitary struggle against nature to the complexities of love and war. Hemingway’s legacy lies in his ability to capture the essence of heroism, making it a relatable and enduring theme in literature.